Identification and remediation of science misconceptions in elementary school teachers using the P2OC2R model - Muslimin Ibrahim; Sunanto Sunanto (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2022)
This study aims to identify the conceptions of elementary school science teachers on 40 science concepts that were found to have misconceptions in the field. Identification of the teacher's conception using the three tiers instrument that had been developed previously, then remediation was carried out using the P2OC2R learning model. Forty science concepts were then tested on eleven teachers. Initially the three tiers instrument was launched to the participants, then the test results were mapped in the form of a conception profile describing the distribution of respondents who understood the concept, did not understand the concept and misconceptions. The next stage, the teachers were carried out learning using P2OC2R learning with the stages of exploring the teacher's initial conception using probing questions, testing the teacher's initial conception through observation of concept examples, negotiating and confirming the conception and reflection for 40 concepts. Furthermore, respondents were tested again using three tiers instruments. The results showed that there had been a change in conception from not understanding the concept and misconceptions to understanding the concept reaching 75.5%. The implication of this research is the action to remediate misconceptions because this research has been able to find the reliability and effectiveness of P2OC2R.Abstrak Penelitian ini bertujuan untuk mengidentifikasi konsepsi guru IPA SD pada 40 konsep IPA yang ditemukan miskonsepsi di lapangan. Identifikasi konsepsi guru menggunakan instrumen three tiers yang telah dikembangkan sebelumnya, kemudian dilakukan remediasi dengan menggunakan model pembelajaran P2OC2R. Empat puluh konsep IPA kemudian diujicobakan pada sebelas guru. Awalnya instrumen three tiers diluncurkan kepada peserta, kemudian hasil tes dipetakan dalam bentuk profil konsepsi yang menggambarkan sebaran responden yang paham konsep, tidak paham konsep dan miskonsepsi. Tahap selanjutnya guru melaksanakan pembelajaran menggunakan pembelajaran P2OC2R dengan tahapan menggali konsepsi awal guru menggunakan pertanyaan probing, menguji konsepsi awal guru melalui observasi contoh konsep, negosiasi dan konfirmasi konsepsi serta refleksi untuk 40 konsep. Selanjutnya responden diuji kembali dengan menggunakan instrumen three tiers. Hasil penelitian menunjukkan bahwa telah terjadi perubahan konsepsi dari tidak memahami konsep dan miskonsepsi menjadi memahami konsep mencapai 75,5%. Implikasi dari hasil penelitian ini adalah adanya kemudahan dalam melakukan remediasi miskonsepsi dengan adanya model remediasi yang disebut Model P2OC2R.